Modelling maternal obesity: the effects of a chronic high-fat, high-cholesterol diet on uterine expression of contractile-associated proteins and ex vivo contractile activity during labour in the rat - Muir, Ronan; Ballan, Jean; Clifford, Bethan; McMullen, Sarah; Khan, Raheela; Shmygol, Anatoly; Quenby, Siobhan; Elmes, Matthew (Portland Press, 2015)
Maternal obesity is associated with prolonged and dysfunctional labour and emergency caesarean section, but the mechanisms are unknown. The present study investigated the effects of an adiposity-inducing high fat, high-cholesterol (HFHC) diet on uterine contractile associated protein (CAP) expression and ex vivo uterine contractility in term non-labouring (TNL) and term labouring (TL) rats. Female rats were fed either control chow (CON n = 20) or HFHC (n = 20) diet 6 weeks before conception and during pregnancy. On gestational day 21(TNL) or day 22 (TL) CON and HFHC (n = 10) rats were killed to determine plasma cholesterol, triacylglycerol and progesterone concentrations and collection of myometrium for contractility studies and expression of CAPs caveolin-1 (Cav-1), connexin-43 (CX-43) and it’s phosphorylated form (pCX-43), oxytocin receptor (OXTR) and cyclooxygenase-2 (COX-2). HFHC feeding increased visceral fat (P 0.001), plasma cholesterol (P 0.001) and triacylglycerol (P = 0.039) concentrations. Stage of labour effected uterine expression of CAV-1 (P < 0.02), pCX43 and COX-2 (both P < 0.03). CAV-1 and pCX43 decreased but COX-2 increased with parturition. Significant diet- and labour-stage interactions were evident for CX-43 and pCX43 (P < 0.03 and P < 0.004 respectively). CX-43 decreased with TL in HFHC animals but was unaltered in CON. pCX-43 fell with labour in CON but remained high in HFHC. OXTR expression was significantly higher in HFHC compared with CON animals (P < 0.03). Progesterone was higher in HFHC rats at term (P < 0.014) but fell significantly with labour to similar concentrations as CON. Contractility studies identified synchronous contractions of stable amplitude in lean animals, but unstable asynchronous contractions with obesity. Uterine dose response to oxytocin was blunted during labour in HFHC rats with a log EC50 of −8.84 compared with −10.25 M in CON for integral activity (P < 0.05). In conclusion, our adiposity model exhibits adverse effects on contractile activity during labour that can be investigated further to unravel the mechanisms causing uterine dystocia in obese women.